Political Jargon as a Form of Doublespeak in the 2024 Presidential Candidates’ Debate” - Smeer, Zeid B.; Nurhadi; Abul Ma’ali; Hermi Ismawati; Fitrotulloh, Mohamad Rofik (INJECT (Interdisciplinary Journal of Communication), 2026)
This study examines the use of jargon in Indonesia’s 2024 presidential debate using William Lutz’s Doublespeak theory. It identifies the forms and functions of political jargon as rhetorical tools to frame political realities and influence public opinion. Using a qualitative descriptive approach and ethnography of communication, the study analyzes transcripts from the first official debate (December 12, 2023). Findings reveal that Anies Baswedan used the most jargon (37.37%), followed by Prabowo and Ganjar (31.31% each). Jargon serves to build credibility while obscuring policy substance through technocratic language. Thus, jargon operates as doublespeak that shapes perception and legitimizes political power.